Changing the Importance of Poland in the Security Policy of the United States in the Context of the war in Ukraine - Jureńczyk, Łukasz (Wydział Nauk Politycznych i Dziennikarstwa UAM, 2023)
The aim of the paper is to analyze and evaluate the changes in the importance of Poland in the security policy of the United States after the outbreak of the war in Ukraine in 2022. The paper consists of two parts. The first one covers the importance of Poland in the US security policy after the Cold War, and the second the change of this importance after the outbreak of the full-scale war in Ukraine. The main research problem is the question of whether Poland’s importance in the US security policy has increased in connection with the Russian aggression on Ukraine? The thesis assumes that the war in Ukraine increased the importance of Poland in American security policy. This is due to three basic premises: Poland has become the main hub for American weapons supplied to Ukraine; Poland plays a key role in humanitarian support for Ukrainian refugees; and the dynamic development of the Polish army increases its importance in the defense of NATO’s eastern flank. Paradoxically, in the context of Polish-American relations, the outbreak of the war turned out to be beneficial for Poland, as earlier it was in danger of cooling down its relations with the USA in connection with the problems with adhering to the principles of the democratic state of law. Currently, this issue is overshadowed by the intensified US-Polish cooperation to help Ukraine and secure NATO’s eastern flank. The research involved interviews with scientists and analysts from scientific centers in Washington and New York.

Celem artykułu jest analiza i ocena zmiany znaczenia Polski w polityce bezpieczeństwa Stanów Zjednoczonych po wybuchu wojny w Ukrainie w 2022 roku. Artykuł składa się z dwóch części. Pierwsza obejmuje znaczenie Polski w polityce bezpieczeństwa USA po zimnej wojnie, a druga zmianę tego znaczenia po wybuchu pełnoskalowej wojny na Ukrainie. Główny problem badawczy zawiera się w pytaniu, czy w związku z rosyjską agresją na Ukrainę wzrosło znaczenie Polski w polityce bezpieczeństwa USA? Teza zakłada, że wojna w Ukrainie spowodowała wzrost znaczenia Polski w amerykańskiej polityce bezpieczeństwa. Wynika to z trzech podstawowych przesłanek: Polska stała się głównym hubem dla amerykańskiego uzbrojenia dostarczanego na Ukrainę; Polska odgrywa kluczową rolę we wsparciu humanitarnym ukraińskich uchodźców; oraz dynamiczny rozwój polskiej armii zwiększa jej znaczenie w obronie wschodniej flanki NATO. Paradoksalnie w kontekście stosunków polsko-amerykańskich wybuch wojny okazał się być korzystny dla Polski, gdyż wcześniej groziło jej schłodzenie stosunków z USA w związku z problemami z przestrzeganiem zasad demokratycznego państwa prawa. Obecnie kwestia ta jest przyćmiona przez zintensyfikowaną współpracę amerykańsko-polską na rzecz pomocy Ukrainie i zabezpieczenia wschodniej flanki NATO. W ramach badań przeprowadzono wywiady z badaczami i ekspertami z ośrodków naukowych z Waszyngtonu i Nowego Jorku.
Zmiana znaczenia Polski w polityce bezpieczeństwa Stanów Zjednoczonych w kontekście wojny w Ukrainie
Keywords: United States; Poland; security policy; war in Ukraine; Stany Zjednoczone; Polska; polityka bezpieczeństwa; wojna w Ukrainie